The preclinical gap in pancreatic cancer and radiotherapy - Tesson, Mathias; Morton, Jennifer P. (Disease models & mechanisms, 2024)
Pancreatic ductal adenocarcinoma is an aggressive malignancy with limited treatment options. Chemotherapy offers little benefit and, although there is some evidence that radiotherapy may improve response, its use in the clinical management of pancreatic cancer remains controversial due to conflicting reports on its survival benefit. There has also been a lack of clinical trials that directly investigate the efficacy of radiotherapy in pancreatic cancer. The limited progress in the development of radiotherapeutic strategies in pancreatic cancer can be attributed, at least in part, to a dearth of preclinical research and our limited understanding of the effects of radiation on the pancreatic tumour microenvironment. In this Perspective, we discuss how insight into the immunosuppressive tumour microenvironment and the complex signalling between tumour and stromal cells following radiation is needed to develop effective radiosensitising strategies for pancreatic cancer. We also highlight that to have the best chance for successful clinical translation, more preclinical research is required in appropriately complex models.